The Mindfulness Meditation Effect on Anxiety in nursing Students level II of nursing study Program STIKes Santa Elisabeth Medan 2022 - Mestiana Br. Karo; Ance Siallagan; Bina Borta Pandiangan (Institute of Computer Science (IOCS), 2022)
Mindfulness meditation is an intervention with mindfulness and mind exercises that aims to relax the mind, increase concentration, and find joy and joy. Mindfulness meditation can reduce anxiety. Anxiety is a psychological and physiological state that is disturbed, due to excessive feelings of a stressor that appears, so that it can cause cognitive, somatic, emotional and behavioral discomfort accompanied by symptoms such as feelings of sadness, emptiness, hopelessness, guilt, worthlessness. irritability, restlessness, loss of interest in activities even though they are pleasurable. This study aims to identify the Mindfulness Meditation Effect on Anxiety in nursing Students level II of nursing study Program STIKes Santa Elisabeth Medan 2022. This research method uses a one group pretest-posttest design. The sampling technique was purposive sampling with a total of 47 respondents. The results of the statistical test showed that there was an effect of mindfulness meditation on anxiety in sophomore students at the Santa Elisabeth Medical School Study Program, Medan in 2022 with the results of the Wilcoxon sign rank test, obtained p value = 0.001. Mindfulness meditation as an alternative to dealing with anxiety in students can reduce students' anxiety levels thereby increasing concentration and relaxing the mind..Further researchers are advised to conduct research on mindfulness meditation with the duration and frequency of the intervention extended by 2-3 cycles to make it more optimal.